What is Legal Theory? - Auer, Marietta (2023)
In recent years, legal theory has developed into a generic term for multidisciplinary legal thinking. Under the heading of legal theory, scholars have explored novel pathways to legal research by using insights and methodologies from a multitude of research fields ranging from cultural studies and economics to genetics and neuroscience. This development stands in contrast to the classic field definition of 20th-century legal theory and 19thcentury general jurisprudence. The classic view conceived both legal theory and its precursor, general jurisprudence, as deliberately anti-philosophical approaches to theoretical reflection on the general structures of positive law. More recently, however, a shift in the internal structure as well as the epistemic aims of legal scholarship has taken place. The present article analyses this development within the framework of the history and philosophy of science. It suggests that interdisciplinary knowledge is a vital and indeed intrinsic part of legal scholarship. An unchartered space nevertheless remains between the disciplinary and the multi-, inter- and transdisciplinary forms of legal knowledge. The recent shift in the research agenda of legal theory highlights this theoretical vacuum, and it is precisely here that the present article situates the potential for a philosophically sophisticated legal theory. It argues that legal theory can best fulfil its goal if it provides tools for multidisciplinary theorising as well as categories for critical reflection on the preconditions of legal epistemology. This essay thus presents legal theory as a philosophical theory of multidisciplinary jurisprudence.